Efektivitas Penambahan Tablet Tambah Darah Pada Peningkatan Nilai Hemoglobin Siswi SMPN 23 Mataram - Aini; I Gde Narda Widiada; Jumari Ustiawaty; Ariyani Ayu Maulana (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Background: Anemia is a disease caused by low hemoglobin levels. Anemia in adolescent girls is a problem that must be addressed immediately, because anemia in adolescent girls is at risk of becoming anemia in pregnant women. Pregnant women who suffer from anemia are not only at risk of giving birth to babies with low birth weight (LBW), but also have the potential to experience complications during pregnancy and childbirth, even death for the mother and child. Objective: To determine hemoglobin levels in teenage students of SMPN 23 Mataram who consume blood supplement tablets. Method: The research method used was cross sectional analytical with research procedures, namely that the researcher carried out direct collection and examination of a sample of respondents who had consumed blood supplement tablets. Results: The overall results obtained from 30 (100%) samples were 4 (15%) samples that were indicated as positive for anemia and the remaining 26 (85%) samples were declared negative for anemia. Conclusion: From the percentage of results obtained, it is said that administering blood supplement tablets which are consumed regularly in accordance with applicable procedures is indicated to be successful in increasing hemoglobin levels in the blood of female students at SMPN 23 Mataram.